PENGARUH PERENDAMAN MENGGUNAKAN LARUTAN CAMPURAN TEMBAGA SULFAT DAN NIKEL NITRAT TERHADAP WARNA PERMUKAAN BAMBU Gigantochloa apus Kurz. - Barly; Susilawati (Jurnal Penelitian Hasil Hutan, 2012)
Bamboo eschibits changes of its attractive green-colored skin inta ivory yellow. Bamboo colour wall turn into dark grey when immersed in water or kept in damp place. Consequently, an attempt is required to prevent such color changes on the surface of bamben skin. This remarch looks into the effectiveness of copper sulfate and nickel nitrate mixture in water based solution to maintain the green color on the skin surface of hambos (Gigantochloa apus Kurtz). The solution is employed in various proportions (w/w) and concentrations. Color innrpretation on the bamboo-skin surface wat assisted wting the so-called CDX's enfor difference meter device based on three-dimensional CIE (L*a*,*) principle. It turned out that intensity of green color on the skin of bamboo trunk at its top (upper) portion and middle portion was greaterthan that of the butt (lower) portion. Furfber, the use of copper culfate nickel nitrate miscture mlution at 4.0:3.5 proportion and in 7.5% concentration inflicted the greatest intensity of green color (", ", and be in average consecutively 61.8, -14.3, and 18.3) on the bamboo-skin, and concurrently afforded the inat prevention of such green color.